Correlation between gross alpha and beta activity concentration in soil samples with dose rates in Iskandar Malaysia, Johor, Malaysia - Abu Hanifah, Noor Zati Hani (2014)
The objective of this study was to determine the gross alpha and gross beta activity concentrations in soil samples collected in Iskandar Malaysia, Johor, Malaysia. A total of 32 soil samples were collected and the dose rates at the location were measured 1 m above the ground. The gross alpha activity concentration ranged from 140 to 2,010 Bq kg-1 with the mean value of 796 ± 70 Bq kg-1. The gross beta activity ranged from 40 to 2,300 Bq kg-1 with the mean value of 837 ± 30 Bq kg-1. The results of analysis show strong correlation between gross alpha activity concentration and dose rate (R = 0.90) and gross beta activity concentration and dose rate (R = 0.84).